Tino rangatiratanga in post-treaty settlement Aotearoa: Challenges of co-governance, and evolving treaty partners - Erueti, Andrew (PUBLIC LAW REVIEW, 2025)
This article considers the puzzle of the location of tino rangatiratanga in the post-Treaty settlements era in the context of current controversy in New Zealand over recognising Maori self-determination or tino rangatiratanga as guaranteed by Art 2 of the Treaty of Waitangi. On one level, the current political and legal struggles reflect a fundamental tension between Maori aspirations for tino rangatiratanga and the state's desire to maintain centralised sovereignty. At a deeper level, the government opposition to co-governance stems from questions about the evolving role of the Treaty - in particular the guarantee of tino rangatiratanga and its ability to apply to a much wider range of Treaty issues (other than natural resources) and Treaty partners; for example, non-tribal Maori collectives serving urban Maori and not bound like tribes by kinship ties. The Waitangi Tribunal, originally established to facilitate Treaty settlements, is now at the centre of this shift in thinking to expand the interpretation of tino rangatiratanga. In a recent series of reports, the Tribunal has recognised the diversity of Maori identity and the legitimacy of non-tribal collectives as Treaty partners, particularly when these organisations are created by and responsive to the socio-economic needs of Maori. The proliferation of Treaty partners thus raises issues of co-ordination and coherence - how do these many partners engage effectively with the Crown and is every Maori organisation a Treaty partner for the purposes of Art 2 tino rangatiratanga? And does provision of social services by these Treaty partners violate the right to equality?
Keywords: Decision making–Evaluation; Equality; Māori (New Zealand people)–Civil rights; Race discrimination; Reparation (Criminal justice); Sovereignty; Treaty of Waitangi

Ram raiding the colony: Māori youth crime in capitalist ideology - Rākete, Emmy; Cox, Kendra (2025)
The 2023 New Zealand general election was marked by media narratives about a youth crime crisis, with special emphasis placed on ram raids and the Māori children and young people blamed for perpetrating them. We show that empirical data do not support the claim that youth crime is surging, and argue that fears of ram raids tap into longstanding beliefs about Māori. Using archival sources from the era of early European settlement in Aotearoa, we show that Pākehā settlers constructed Māori children and young people as uniquely dangerous delinquents. Using Louis Althusser’s theory of ideology and subjectivation, we argue that this delinquentisation played a key role in constituting a colonial ideology that would justify primitive accumulation, colonisation, and the imposition of the capitalist mode of production in Aotearoa. Looking to the contemporary neoliberal era, we argue that moral panics about ram raids continue this colonial ideology of delinquentisation. By subjectivating children and young people as delinquents, the capitalist class is able to use the criminal justice system to displace responsibility for the crisis of social reproduction precipitated by neoliberal economic policy. We conclude by showing the limitations of this strategy and arguing for intensified struggle against the ideology of delinquentisation.

The double trusteeship of Te Tiriti o Waitangi: Pā to Plate and the sixth Labour government - Kawharu, Merata; Tapsell, Paul (Political Science, 2025)

Barriers to and opportunities for the restoration of mana in emergency management legislation and its implementation for Māori - Reid, John; Awatere, Shaun; Rout, Matthew; Campbell, Emily; Huang, Annie; Warmenhoven, Tui (Disasters, 2025)
Ever since colonisation by the British in 1840, Māori, the indigenous peoples of Aotearoa New Zealand, have been fighting to reclaim their mana (authority and influence) over their whenua (land). They were set to regain mana in emergency management (EM) through a parliamentary Bill, but a recent change of government has seen this legislation discharged. This paper explores the barriers to and the opportunities for gains in authority and influence in EM, with authority understood as representation on the national and regional EM bodies, and influence as incorporation of the Māori worldview into legislation and supporting EM implementation documentation. The study applies these different levels of analysis to two case studies to examine any EM-related changes between the Christchurch earthquake in February 2011 and the arrival of Cyclone Gabrielle in February 2023. The paper offers several strategies at both analytical levels that Māori could use to further their mana under the current government.
Keywords: Aotearoa; Māori; New Zealand; disaster risk reduction; emergency management; legislation

Indigenous Representational Choices: Results from a Large Qualitative Survey on Māori Electoral Roll Choice - Greaves, Lara Marie; Hini, Rebecca; Overbye, Hannah R.; Brink, Kaylee Grace (Journal of Race, Ethnicity, and Politics, 2025)
Different participatory mechanisms for the representation of Indigenous peoples have been proposed across states. Since their creation in 1867, the Māori electorates in the national Parliament have led to dedicated representation for Māori (Indigenous peoples of New Zealand). However, only half of Māori choose to vote on the Māori roll, the remainder choosing to vote on the General roll, illustrating that roll choice is not based simply on group representation. This survey aimed to ask Māori (N = 1,958) in their own words why they made their roll choice. Through a deductive codebook thematic analysis, a range of codes were constructed around the reasoning behind roll choice. Māori on the Māori roll made their choice because they valued Māori representation; as an expression of their identity; to support the electorates; as a strategic choice; or they had been influenced by others or through education. Those on the General roll felt their roll was the default or a more familiar option; the Māori roll had less of an impact; it was a strategic choice, or they appreciated greater candidate variety; or they valued the smaller geographic electorate size. Some felt Māori no longer needed separate representation or felt less connected to their identity as Māori. The results have implications for both Māori and Indigenous representation through dedicated representational mechanisms.
Keywords: Indigenous; Māori; Māori electorates; Voting; Parties; Parliament; representation; voter enrolment